2005
DOI: 10.1262/jrd.16055
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunization against Inhibin Improves Superovulatory Response to Exogenous FSH in Cattle

Abstract: Abstract. The effect of active immunization against inhibin on the response to superovulatory treatment by porcine FSH (pFSH) was investigated in cattle. Japanese black cows were sc injected with 1 mg of porcine inhibin α-subunit fragment (1-26) conjugated with rabbit serum albumin (inhibin-immunized group; n=14) or rabbit serum albumin alone (control group; n=12) in Freund's complete adjuvant. Booster injections (half the amount of the primary injection) were given 35 and 70 days after the primary injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
(28 reference statements)
3
13
1
Order By: Relevance
“…The yields of CL were increased gradually from 8.60±0.60 to 14.80±0.66 indicating a clear impact of FSH dose levels on CL production in Local genetic group (Table 1). The CL yields in Local genetic group with FSH observed in the present study were in agreement with the findings of Elsden et al (1978), Chupin and Procureur (1983), Yaakub et al (1999) and Takedomi et al (2005), but were higher than those reported by Sugano and Shinogi (1999). The yields of both the recovered embryos (RE) and transferable embryos (TE) showed significantly highest yields in the 280 mg of FSH dose level and thereafter decreased gradually indicating significant impact of 280 mg dose level of FSH on the production of transferable embryos in Local genetic group relating to dose specific response which might be influenced by the genotype and body weight of the experimental donor cows and the day of superovulation induction.…”
Section: Resultssupporting
confidence: 92%
“…The yields of CL were increased gradually from 8.60±0.60 to 14.80±0.66 indicating a clear impact of FSH dose levels on CL production in Local genetic group (Table 1). The CL yields in Local genetic group with FSH observed in the present study were in agreement with the findings of Elsden et al (1978), Chupin and Procureur (1983), Yaakub et al (1999) and Takedomi et al (2005), but were higher than those reported by Sugano and Shinogi (1999). The yields of both the recovered embryos (RE) and transferable embryos (TE) showed significantly highest yields in the 280 mg of FSH dose level and thereafter decreased gradually indicating significant impact of 280 mg dose level of FSH on the production of transferable embryos in Local genetic group relating to dose specific response which might be influenced by the genotype and body weight of the experimental donor cows and the day of superovulation induction.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, use of passive or active immunization against inhibin is a suitable, simple, and practical alternative to eCG for induction of superovulation in goats. Moreover, active i m m u n i z a t i o n a g a i n s t i n h i b i n i m p r o v e s superovulatory response to exogenous FSH in cattle [27]. In the present study, the ovulation rate was not comparable to the follicular population.…”
Section: Discussioncontrasting
confidence: 73%
“…Multiple ovulations have been induced successfully by passive immunization against endogenous inhibin in several species, such as rats [1], ewes [19,20], hamsters [12], cows [21,22], mares [10], guinea pigs [13], mice [23], and goats [24,25]. Also, active immunization against inhibin has been used in cows [26][27][28], goats [29], ewes [30], and mares [31]. T h u s , t h e s e i n i t i a l r e s u l t s i n d i c a t e t h a t immunization of animals against endogenous inhibin to induce superovulation through increased endogenous FSH secretion is an alternative method to the current exogenous gonadotropin protocols.…”
mentioning
confidence: 99%
“…Also, although Inhbb expression was up‐regulated after Inha silencing, the secretion of Inhibin β is still decreased (Han et al, ), indicating how important their co‐production is. Interestingly, inhibin vaccines that attenuate its activity resulted in higher fertility and ovulation rates in sheep, cattle, and rats (Dan, Liu, Han, Liu, & Yang, ; Han et al, ; Takedomi et al, ). Activin, on the other hand, enhances the secretion of FSH, and is a promoter of FSHR expression within pituitary cells (Thackray, Mellon, & Coss, ).…”
Section: Discussionmentioning
confidence: 99%